Tenchi Seikyō: A Messianic Buddhist Cult - Pearce, Thomas H. (Japanese journal of religious studies, 1994)
Tenchi Seikyō is a small New Religion in Japan that has converged with the Unification Movement of Rev. Sun Myung Moon. This paper presents the history and nature of Tenchi Seikyō, describes the life of its founder, Kawase Kayo, and outlines Tenchi Seikyō's organization, beliefs, and practices. It also discusses the symbiotic relationship between Tenchi Seikyō and the Unification Movement (Jpn. Tōitsu Undō), and the reasons for the two organizations to develop such a relationship.